Anterior Laxity at 2 Years After Anterior Cruciate Ligament Reconstruction Is Comparable When Using Adjustable-Loop Suspensory Fixation and Interference Screw Fixation. Issue 10 (August 2018) - Boutsiadis, Achilleas; Panisset, Jean-Claude; Devitt, Brian M.; Mauris, Frédéric; Barthelemy, Renaud; Barth, Johannes
Background: Adjustable-loop suspensory fixation (ALSF) devices are commonly used in anterior cruciate ligament reconstruction (ACLR). However, concern exists regarding the potential for lengthening under cyclical loads. Purpose: To compare the residual anterior laxity of 2 methods of femoral fixation, ALSF versus interference screw fixation, in patients undergoing isolated ACLR in the absence of meniscal injuries. To determine the preoperative risk factors associated with residual postoperative anterior laxity. Study Design: Cohort study; Level of evidence, 3. Methods: A retrospective analysis was performed comparing 2 groups of patients that underwent primary ACLR using ALSF versus bioabsorbable interference screw fixation. Anterior knee laxity was assessed with Telos stress radiography, while functional outcomes were evaluated with the Knee injury and Osteoarthritis Outcome Score (KOOS) and Tegner activity level scale at a minimum of 2 years postoperatively. A multivariate analysis was performed to identify factors associated with residual postoperative laxity >3 mm. Results: Of the 1136 patients who underwent ACLR during the study period, 363 met the inclusion criteria. A total of 272 patients (75%) (mean age, 31.7 ± 10.7 years) with a mean follow-up of 25.7 ± 4.6 months (range, 24-36 months) consented to participate (screw group: n = 121; ALSF group: n = 151). The 2 groups were statistically comparable in terms of age, sex ratio, time from injury to surgery, graft diameter, preoperative laxity, preoperative objective International Knee Documentation Committee (IKDC) grade, and preoperative Tegner score. The mean postoperative laxity as a continuous variable was significantly different comparing the ALSF and screw groups (1.49 ± 1.98 mm and 2.32 ± 1.97 mm, respectively; P < .001). In the screw group, 76 patients (62.8%) had normal (<3 mm), 40 (33.1%) had nearly normal (3-6 mm), and 5 (4.1%) had abnormal (≥6 mm) postoperative knee laxity according to the IKDC grade, while in the ALSF group, 112 patients (74.2%) had normal, 37 (24.5%) had nearly normal, and 2 (1.3%) had abnormal laxity ( P = .0833). No significant difference was found in KOOS or Tegner scores comparing the 2 femoral fixation methods: KOOS, 90.6 ± 7.5 (ALSF group) and 90.6 ± 7.4 (screw group) ( P = .7631), versus Tegner, 6.5 ± 1.3 (ALSF group) and 6.3 ± 1.4 (screw group) ( P = .2992). A negative correlation was found between postoperative laxity and final Tegner ( r s = −0.303, P < .001) and KOOS scores ( r s = −0.168, P = .005). The initial univariate analysis showed differences between groups of patients with residual knee laxity ≥3 mm and <3 mm on preoperative pivot shift, preoperative laxity, age, fixation type, and preoperative objective IKDC grade. The multivariate analysis on these factors showed that the pivot shift remained the only significant predictor for residual laxity ≥3 mm for pivot shift grade 2 compared with grade 1 (odds ratio, 4.689 [95% CI, 2.465-9.286]) and for pivot shift grade 3 compared with grade 1 (odds ratio, 58.025 [95% CI, 12.757-557.741]) ( P < .001). Conclusion: For primary ACLR, the use of an ALSF device for femoral fixation is associated with noninferior postoperative anterior knee laxity results compared with interference screw fixation at a minimum 2 years' follow-up. The preoperative pivot shift is the only significant risk factor for postoperative residual anterior knee laxity >3 mm.